Green Approach: ‘‘A Forwarding Step for Curing Leishmaniasis—A Neglected Tropical Disease’’ - Sharma, Lakshika; Dhiman, Mamta; Singh, Abhijeet; Sharma, M. M. (Frontiers in Molecular Biosciences, 2021)
The present review focuses on a dreaded vector mediated leishmaniasis- the existing therapeutic approaches including a variety of drugs along with their limitations, the treatment with natural compounds and the different type of metal/metal oxide nanoparticles (NPs). As evidenced various metallic NPs comprising silver, silver oxide, gold, zinc oxide, titanium, lead oxide etc. played a curative role to treat leishmaniasis, is also presented. Keeping in view the advance success of vaccines against the prevalent dreaded diseases in the past and the present scenario, efforts are also being made to develop vaccines based on these NPs formulations.